2023
DOI: 10.1002/ppsc.202200193
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Hybrid Dendrimers and Their Generations for Modulated Spatio‐Temporal Action

Abstract: Hybrid dendrimers constitute a unique class of well-defined complex architecture featured with a central domain and bifurcated branches with two different dendritic sequences for their atomic configuration and functional groups at the periphery. This review article pioneers the field of new hybrid dendrimers using different generations by nanoconjugation with metals, carbohydrates, nucleotides, proteins/peptides, carbosilane, urea, silica, stem cells, guanidine, etc. The smart dendrimers contain desirable elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 100 publications
0
0
0
Order By: Relevance
“…A polymer drug delivery system is defined as a preparation or device that efficiently introduces therapeutic substances into a specific targeted location [24]. Numerous studies have demonstrated that polymer drug delivery systems can achieve continuous drug delivery to the eye, effectively enhancing the bioavailability and compliance of drugs [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…A polymer drug delivery system is defined as a preparation or device that efficiently introduces therapeutic substances into a specific targeted location [24]. Numerous studies have demonstrated that polymer drug delivery systems can achieve continuous drug delivery to the eye, effectively enhancing the bioavailability and compliance of drugs [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%